Transformasi dan Marginalisasi Masyarakat Adat: Suku Ata Modo di Tengah Hegemoni Pengembangan Pariwisata Taman Nasional Komodo (Transformation and Marginalization of Indigenous Communities: The Ata Modo Tribe's Experience Amidst the Hegemony of Komodo National Park Tourism Development) - Pratama, Arif Putra; Chandra, Avicenna Elang; Isnanto, Noor Risa; Nisa, An Nuur Khairune (The Indonesian Journal of Socio-Legal Studies, 2024)
The massive development of tourism in Komodo National Park (KNP) has had a signi;icant impact on the local community there, in this case the Ata Modo Tribe. This tribe is a local tribe that has remained silent for a long time and was formed on Komodo Island long before the Komodo National Park was established. They have also lived side by side with the endangered Komodo dragon for decades and tried to maintain their culture and customs amidst the existence of KNP tourism development. This research tries to answer what cultural potential is still maintained by the Ata Modo Tribe, the position of the Ata Modo Tribe as a Customary Law Community unit, as well as the socio-economic, cultural and environmental impacts that occur amidst KNP tourism hegemony. The study in this research uses a type of socio-legal research. Various primary and secondary data were formulated and analyzed to obtain descriptive conclusions for each problem formulation question. The research results obtained are ;irst that the Ata Modo tribe has cultural potential in accordance with the seven elements of culture consisting of language, knowledge system, social organization, technology, livelihood system, belief system and art. Second, the absence of recognition and determination of the Ata Modo Tribe as a Customary Law Community unit through legal products at the regional level provides opportunities for conflicts of interest and override of their customary rights. Third, the Ata Modo tribe has transformed coercively due to the existence of KNP tourism. Regulations established as a means of conservation of the Komodo National Park encourage a coercive transformation of the culture of the Ata Modo people. Keywords: Coercive Transformation, Customary Law Communities, Marginalization, Ata Modo Tribe